PENERAPAN MODEL ROLE PLAYING UNTUK MENINGKATKAN EMPATI DAN PRESTASI BELAJAR (PTK Pada Mata Pelajaran PKn Siswa Kelas II SD Gugus IV Bengkulu Selatan) - Insyi Novlita; Johanes Sapri (DIADIK, 2020)
This study aims to: (1) describe the application of the Role Playing model in increasing the empathy of class II students of Cluster IV South Bengkulu. (2) Describe the application of the Role Playing model in improving student achievement in class II Cluster IV South Bengkulu. (3) Describe the effectiveness of the application of the role playing model in improving student achievement in class II Cluster IV South Bengkulu. This research is a classroom action research (CAR) which is then followed by experiments. The method used is a quasi-experimental method. The subjects of this study were the second grade students of SDN 64 South Bengkulu, which amounted to 17 people. The design at this writing is The Matching Only Pretest-Posttes Control Group Design. The population in this study was class II students in Cluster IV South Bengkulu. The sample in writing is class II SDN 64 Bengkulu Selatan totaling 17 people as the experimental class and class II SDN 58 Bengkulu Selatan as the control class. The instruments used were observation sheets and written test sheets. The results showed that there was an increase in students' empathy and learning achievement by using a role playing model in Civics subjects for grade II students in cluster IV, South Bengkulu.